2006
DOI: 10.1186/1477-7819-4-68
|View full text |Cite
|
Sign up to set email alerts
|

Distress, anxiety, and depression in cancer patients undergoing chemotherapy

Abstract: Background: Chemotherapy for cancer is an intense and cyclic treatment associated with number of side-effects. The present study evaluated the effect of chemotherapy on distress, anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
84
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 12 publications
11
84
3
2
Order By: Relevance
“…In the studies of Gozum and Akçay, 53.2% of Turkish cancer patients receiving chemotherapy were reported to be depressive [13]. Pandey et al found depression to be present in 16.2% of cancer patients undergoing chemotherapy [14]. Tsunoda et al reported that 36.7% of colorectal cancer patients were depressive [15].…”
Section: Discussionmentioning
confidence: 97%
“…In the studies of Gozum and Akçay, 53.2% of Turkish cancer patients receiving chemotherapy were reported to be depressive [13]. Pandey et al found depression to be present in 16.2% of cancer patients undergoing chemotherapy [14]. Tsunoda et al reported that 36.7% of colorectal cancer patients were depressive [15].…”
Section: Discussionmentioning
confidence: 97%
“…From the time of diagnosis, the cancer patients experience different types of mental distress and adaptation to the process of cancer treatment including investigation, waiting for results, planning for surgery, chemotherapy, hormonal therapy, radiotherapy and recovery [23,24]. Interestingly, the result of a study by Kristin et al in postsurgery breast cancer patients showed that QoL improved over the first 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…The Distress Inventory for Cancer (DIC) since its first publication [32] has been substantially revised [33][34][35][36]. The data from a large sample of patients that had responded to the DIC version 2 were the basis, on which the present study is reported.…”
mentioning
confidence: 99%